DESENTRALISASI FISKAL: STUDI TENTANG PEMERINTAH KOTA PEKANBARU DALAM PENYERAPAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) TAHUN 2014 - Rezeki, Nofa Sapitri; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was motivated by Pekanbaru City budget continues to increase significantly each year. However, the increase in the budget is not directly proportional to the ability of the government to absorb the budget, every year countless SiLPA large numbers. This study wanted to see how the City of Pekanbaru in Pekanbaru City budget Absorption and what are the factors that influence the Government in Pekanbaru City budget absorption of 2014. This type of research is descriptive qualitative research methods. The research location in the environment SKPD Pekanbaru. Data was collected through interviews and documentation. While data analysis is conducted by using descriptive data analysis. The results of this study are not yet optimal Pekanbaru City Government in the absorption of Pekanbaru City budget year 2014, it can be seen from Pekanbaru City Government expenditure as a whole is 82.44%. SKPD high budget but absorption is also high at the Department of Education and the lowest absorption SKPD that the Regional Secretariat. Pekanbaru City budget is widely used for operational expenditure of capital expenditure. Operational expenditure made up of personnel expenditure realization was 49% and spending on goods and services realization was 21.14%. As for capital expenditures amounted to only 28%. Pekanbaru City capex of total capital expenditures amounted to Rp647 billion, as much as Rp239 billion or 45% was used for capital expenditures that are not directly felt by the public. SKPD most SiLPAnya namely the Department of Education which amounted to 23% of the total SiLPA whole, further SKPD contributor SiLPA high that the Regional Secretariat of 21% of the total SiLPA overall and the last SKPD SiLPAnya height of Highways and Water Resources amounting to 10% of the total SiLPA whole. Only two of 46 SKPD SKPD that its capital expenditures more than on operational expenditure, namely the Department of Highways and Water Resources and the Department of Housing and Human Settlements. Factors that affect the absorption of Pekanbaru City budget in 2014, namely Establishment of Pekanbaru City budget is slow, long tender bidding process, the program will be delayed.Keywords: government, local budget absorption, SiLPA.